A History Of Merdeka Curriculum For English Education In Indonesia - Maulidina Tri Amanda; Akhmad Ali Mirza; Zaitun Qamariah (PT. Padang Tekno Corp, 2023)
The Covid-19 pandemic has been going on for two years and has affected people's life in many different ways, including how the subject of education has affected people. Raising and harmonizing educational standards is a crucial problem for the government's efforts to improve Indonesia's educational system. It is thought that the current curriculum is insufficient to improve education quality, as shown by the indicators of student learning results, which are still low. This claim shows how important it is for educational implementers to use the curriculum as a guide, tool, or document to carry out the best teaching and learning procedures possible in order to achieve educational goals.